Optimization of pancreatic trypsin extraction in PEG/citrate aqueous two-phase systems - Pérez, Rocío Laura (2015)
Enzyme extraction using aqueous two-phase systems (ATPS) has been increasingly used as a primary recovery technique which integrates the clarification, concentration and partial purification of important biomolecules from their natural source in a single step. The goal of this work was to optimize the extraction of trypsin from pancreas homogenate with polyethylene glycol and sodium citrate (PEG/NaCit) ATPS by using the tools of experimental design. The variables NaCl concentration – added inert salt –, the top/bottom phase volume ratio – Vr – and the biomass loaded into the system – in percentage – were selected as the main factors in the trypsin extraction. The yield (%) and the purification factor of trypsin were considered the responses to be optimized. The central composite design and the response surface analysis proved to be suitable tools for a quick and efficient study. As a result, the optimal extraction conditions in PEG3350/NaCit system were 3.34% wt/wt for NaCl concentration, a biomass load which represented 9.30% wt/wt of the total ATPS mass and 6.37 top/bottom volume ratio giving a purification factor of 2.55 and a yield of 99.7% in top phase.